Oral Verruciform Xanthoma: A Case Report and Literature Review. (16th December 2013) - Shetty, Akshay; Nakhaei, Kourosh; Lakkashetty, Yogesh; Mohseni, Maryam; Mohebatzadeh, Iman
Abstract : Verruciform xanthoma is a benign mucocutaneous, uncommon, nonsymptomatic lesion of uncertain etiopathology, which occurs mostly on the oral mucosa of middle-aged individuals. Histopathologically, VX is diagnosed by presence of lipid-laden foam cells in papillary region of connective tissue. A 60-year-old male patient presented with a painless growth on the left buccal mucosa. On clinical examination a yellowish white exophytic lesion, measuring 11 × 7 mm in size, was found, which was cauliflower-shaped on inspection and painless on palpation. Histopathological examination revealed varying degrees of surface parakeratosis and the accumulation of numerous foam cells in the connective tissue papillae among the uniformly elongated epithelial ridges. On immunohistochemical staining, there was a neutrophilic infiltrate of the epidermis with CD68 positive xanthoma cells restricted to the papillary dermis, mixed with other chronic inflammatory cells.